SYNTHESIS, CHARACTERISATION AND ANTI-TUBERCULAR ACTIVITY OF SOME NEW 3,5-DISUBSTITUTED-2,4-THIAZOLIDINEDIONES - Chilamakuru, Naresh Babu (Asian Journal of Pharmaceutical and Clinical Research, 2013)
As per world health organization by 2020, the number of tuberculosis infected patients will be 25% of the world population. Now, it is challenging and essential target for medicinal chemists in drug search for tuberculosis. Hence the present work includes synthesis of a series of 3,5-disubstituted thiazolidine-2,4-dione derivatives by condensation of thiazolidine-2,4-dione with aromatic aldehydes at 5th position-Knoevenagel reaction followed by condensation of these 5-substituted thiazolidine-2,4-diones by using various aromatic and alkali halides at 3rd position yielding to 3,5-disubstituted thiazolidine-2,4-diones. The synthesized 3,5-disubstituted thiazolidine-2,4-dione compounds were characterized by IR, 1H NMR, Mass spectroscopy and CHNO Elemental analysis. The synthesized compounds were predicted for biological activities by using Prediction of Activity Spectra for Substances computerized program-(Insilico method) based on those results the compounds were screened against Mycobacterium tuberculosis H37RV strain in the Middlebrook 7H9 broth by microplate alamar blue assay using Streptomycin and Pyrazinamide as standard drugs. The results revealed that among those synthesized new 3,5-disubstituted thiazolidinediones 3a, 3b, 3e and 3h were showed good antitubercular activity. Keywords: Thiazolidine-2,4-dione, knoevenagel reaction, Mycobacterium tuberculosis, antitubercular activity.